Systematic description of the development of a complex health intervention of information and support in a new pregnancy after pregnancy loss - Emily Koert; Sarah Fredsted Villadsen; Rebecca Mackel; Helene Cagara; Tanja Schlaikjær Hartwig; Henriette Svarre Nielsen; Lone Schmidt (BMC Public Health)
Abstract Background In this paper, we present a systematic description of the development method of a complex health intervention (PREGAFTERPL) for couples with prior pregnancy loss (PL) to provide information and support in a new pregnancy using co-production and prototyping. Methods A three-stage method described by Hawkins et al. and informed by O’Cathain et al. was tested to develop the PREGAFTERPL intervention for couples over a 24 month period. We used a combination of the partnership and theory and evidence based approaches of O’Cathain’s nine categories of intervention development approaches. The stages included: (1) Evidence review, needs assessment and stakeholder consultation, (2) Co-production with stakeholders (health care professionals, researchers and couples with prior pregnancy loss) via consultations and focus groups, and (3) Prototyping using focus group and online survey. The three stage co-production and prototyping process was iterative and cumulative with refinements occurring at each stage before progressing to the next stage. Results Using the three-stage method we co-produced and prototype-tested the intervention content and delivery methods for the PREGAFTERPL intervention. In stage 1 we identified the needs of pregnant women and their partners and potential content of the intervention to include information, coping strategies and tools and resources. In stage 2, multiple refinements of the content and delivery resulted from an action research cycle with input from stakeholders including the decision to divide the tool into one for women and another for partners. Initial prototyping in stage 3 showed that the tools were acceptable, useful and relevant and it was suitable to proceed with full-scale feasibility testing, implementation and evaluation. Conclusions This framework presented in the PREGAFTERPL case study provides a practical example on how to co-produce and prototype a complex healthcare intervention in collaboration with key stakeholders including health care professionals and couples with prior pregnancy loss in order to meet an unmet need for information and support in a new pregnancy after PL. Through such case study, we hope that future researchers will be inspired to include co-production in their own intervention development projects by seeing that it is valuable and can be feasible and done with limited resources. Trial registration Not applicable.